A COMPREHENSIVE STUDY OF CRYPTOGRAPHY AND KEY MANAGEMENT BASED SECURITY IN CLOUD COMPUTING - Vinothkumar, S.; Amutharaj, J.; Jeyabalan, S. (The journal of contemporary issues in business and government, 2021)
Cloud computing is a cost effective flexible and proven delivery platform for providing consumer IT services or business services over internet. It has an ability to provide many services over internet. It not only provides computing services but additional computing resources. To interact with various services in the cloud and to store retrieve data from cloud several security mechanism is required. Cryptography and key management mechanism are one of the import services in the cloud to secure data. In this context, this paper investigates the basic problem of cloud computing with cryptography and key management system for enabling support of interoperability between cloud cryptography client and key management services.